2015
DOI: 10.1515/jpem-2014-0319
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity, thyroid function, and insulin resistance – is there a link? A longitudinal study

Abstract: Background: Serum thyroid stimulating hormone (TSH) levels are frequently elevated in obese children and are most likely to be associated with insulin resistance. However, clinical relevance of this association remains unclear. Objectives: To assess the prevalence of hyperthyrotropinemia; to analyze the relationship between TSH and homeostasis model assessment -insulin resistance (HOMA-IR); and to verify whether TSH levels and HOMA-IR vary with weight loss in obese children. Subjects and Methods: Retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 29 publications
3
27
1
1
Order By: Relevance
“…As shown in our study and in other studies by losing weight TSH levels decreased significantly [9,20,25]. However some studies found no relationship between weight loss and normalization of TSH values [26,27]. Our current knowledge does not support the use of thyroxine treatment for elevated TSH in obese children [28,29].…”
Section: Discussioncontrasting
confidence: 75%
“…As shown in our study and in other studies by losing weight TSH levels decreased significantly [9,20,25]. However some studies found no relationship between weight loss and normalization of TSH values [26,27]. Our current knowledge does not support the use of thyroxine treatment for elevated TSH in obese children [28,29].…”
Section: Discussioncontrasting
confidence: 75%
“…In some studies, weight loss has been reported to normalize TSH levels as well as metabolic parameters of glucose metabolism and lipid profile [22, 23], whereas 1 study did not find an association of TSH with lipid parameters even though TSH was reduced after weight loss [24]. However, despite a large number of studies, it is still unclear whether high TSH levels are compensatory to maintain normal thyroid hormone levels, and it is also unclear whether TSH is associated with metabolic disturbances in children with obesity since previously published research are inconsistent [25].…”
Section: Introductionmentioning
confidence: 99%
“…This leads us to consider the condition a physiological one and to discard the possibility of using levothyroxine to lower TSH levels in overweight or obese children and adolescents in order to reduce associated comorbidities. On the other hand, there are studies which report a significant association between thyrotropin and metabolic syndrome (38,39), carbohydrate intolerance (24), elevated total and LDL cholesterol (21,40), and elevated triglycerides (24,29,33,40) as well as between low levels of free T4 and increased insulin concentration (34). …”
Section: Discussionmentioning
confidence: 99%